Diseño organizacional en las Farmacias Comunitarias en la ciudad de Babahoyo - Pilamunga Gavilanez, Damaris Graciela (2021)
This research is carried out in the Community Pharmacies of the city of Babahoyo, dedicated to the purchase and sale of products related to the pharmaceutical sector with the highest quality standards, which contributes to maintaining optimal well-being and health of the local citizens. The objective of this study was to analyze the organizational structure and how it influences the internal functions of the company, due to the fact that there are problems in the segregation of activities, manual of functions, weak teamwork, organizational management and satisfaction of the services of users effectively. The applied methodology is of a descriptive type, which by means of the implementation of the deductive and inductive methods, the particular situations were collected in detail on the subject analyzed. For this, survey and interview techniques were used that allowed obtaining the following results: Community Pharmacies have a weak organizational structure that prevents them from meeting their planned objectives in a timely manner; In addition, the lack of a manual of functions causes that the distribution or segregation of activities is not adequate, added to the lack of communication, teamwork, outsourcing of tasks, has generated to a certain extent that the satisfaction of care services the customer are not efficient.